Aspectos históricos e jurídicos do segurado especial "trabalhador rural" : na microrregião de Getúlio Vargas/RS - Lang, Lilian Hanel (2012)
The welfare state was born of concern to ensure the livelihood of workers and their dependents in cases of disability or death. It was only with the advent of the Constitution of the Federative Republic of Brazil in 1988 that pension rights were extended to rural workers. It should verify that this audience has enjoyed this legislation and how the perception of a social security benefit can guarantee their dignity